2018
DOI: 10.3390/catal8010041
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Carbon Dioxide Photoreduction by a Cooperative Effect of Reactor Design and Titania Metal Promotion

Abstract: An effective process based on the photocatalytic reduction of CO 2 to face on the one hand, the crucial problem of environmental pollution, and, on the other hand, to propose an efficient way to product clean and sustainable energy sources has been developed in this work. Particular attention has been paid to the sustainability of the process by using a green reductant (water) and TiO 2 as a photocatalyst under very mild operative conditions (room temperature and atmospheric pressure). It was shown that the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 105 publications
0
12
0
Order By: Relevance
“…Therefore, much effort has been focused on enhancing the photocatalytic activity of TiO 2 , including doping with metal or non-metal species [17,18], surface sensitization [19,20], and noble metal deposition [21][22][23][24][25]. In particular, the noble metal deposition has attracted a lot of attention since it can improve e − -h + separation and enhance the semiconductor's absorption in the visible light region [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, much effort has been focused on enhancing the photocatalytic activity of TiO 2 , including doping with metal or non-metal species [17,18], surface sensitization [19,20], and noble metal deposition [21][22][23][24][25]. In particular, the noble metal deposition has attracted a lot of attention since it can improve e − -h + separation and enhance the semiconductor's absorption in the visible light region [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Concerning gas phase reactions, several different reactor configurations have been reported, such as packed bed [244], plate thin-film [170] and coated honeycomb [175], although no direct comparison among them has been done. It is worth observing that reactor design, as reported in Section 2.2, has a crucial role in photocatalysis, since as we recently report for CO 2 photoreduction, a proper irradiation pattern creates higher productivity with lower amounts of catalyst [74]. Nonetheless, there is plenty of work that can be done on PR reactors' design.…”
Section: Photoreactors Designmentioning
confidence: 98%
“…On the contrary, CO 2 photoreduction can also be performed in the gas phase, feeding water as vapour, leading to slightly different results in observed mechanisms. For example, Karamian and co-workers [88] reported that in most cases, in gaseous systems CO is the first intermediate product of CO 2 photoreduction by water vapour [74].…”
Section: Vb : 2hmentioning
confidence: 99%
See 2 more Smart Citations